2021
DOI: 10.1002/ecm.1440
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of hydric and thermal conditions drive geographic variation in thermoregulation in a widespread lizard

Abstract: Behavioral thermoregulation is an efficient mechanism to buffer the physiological effects of climate change. Thermal ecology studies have traditionally tested how thermal constraints shape thermoregulatory behaviors without accounting for the potential major effects of landscape structure and water availability. Thus, we lack a general understanding of the multifactorial determinants of thermoregulatory behaviors in natural populations. In this study, we quantified the relative contribution of elevation, therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 85 publications
(184 reference statements)
0
21
0
Order By: Relevance
“…This is consistent with Clusella-Trullas et al (2011), who found rainfall of the driest month was the best macroclimatic predictor. Soil dryness integrates multiple atmospheric factors as well as soil properties and may be acting as a proxy for vegetation density, which can powerfully constrain thermoregulatory opportunities for ectotherms (Basson et al, 2017;Pike et al, 2011;Rozen-Rechels et al, 2021;Ryan et al, 2016). Likewise, we found stronger correlations of CT max with microclimatic and biophysical predictors, especially soil dryness.…”
Section: Thermal Physiologymentioning
confidence: 56%
See 1 more Smart Citation
“…This is consistent with Clusella-Trullas et al (2011), who found rainfall of the driest month was the best macroclimatic predictor. Soil dryness integrates multiple atmospheric factors as well as soil properties and may be acting as a proxy for vegetation density, which can powerfully constrain thermoregulatory opportunities for ectotherms (Basson et al, 2017;Pike et al, 2011;Rozen-Rechels et al, 2021;Ryan et al, 2016). Likewise, we found stronger correlations of CT max with microclimatic and biophysical predictors, especially soil dryness.…”
Section: Thermal Physiologymentioning
confidence: 56%
“…Yet we did not observe evaporative water loss at the biophysical scale as a strong predictor, which would be most correlated with resistance to water loss if the selective force was simply environmental 'dryness'. However, it is increasingly recognized that lizards can behaviourally regulate their water loss rates (hydroregulation) through microhabitat selection (Huang et al, 2020;Pirtle et al, 2019;Rozen-Rechels et al, 2021;Ryan et al, 2016;Sannolo & Carretero, 2019). The overall water balance depends on both gains (e.g., from food) and losses and it may be that soil dryness is capturing both water availability and water loss in the one metric.…”
Section: Thermal Physiologymentioning
confidence: 99%
“…Although this species typically occupies open habitats (meadows, peatbogs, heathlands) to perform daily activities, mixed habitats with proximity to dense forests might represent more intact habitat landscapes. In addition, lizards in populations next to or mixed with forest patches are better capable of adjusting their breeding phenology (Rutschmann et al., 2016) and their thermoregulation behaviour (Rozen‐Rechels et al, in press). Mixed forest habitats might therefore allow lizards to buffer negative consequences of extreme weather events.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we expected demographic and genetic variation to be negatively impacted by constraining climate conditions and low habitat quality. We tested this prediction by checking the influence of two climate variables (i.e., air temperature and precipitation flux) and two habitats characteristics (i.e., forest cover and wetland potential) that are known to drive ecophysiological adjustments and local adaptations in this species (Dupoué, Rutschmann, Le Galliard, Clobert, et al, 2017; Dupoué, Rutschmann, Le Galliard, Miles, et al, 2017; Lorenzon et al., 1999; Rozen‐Rechels et al, in press; Rutschmann et al., 2016, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Accelerated global warming is causing the eradication of a significant proportion of the global reptile diversity (Sinervo et al 2010;Durán et al 2020). Due to their high species-richness, lizards constitute a major group of conservation concern (e.g., Sinervo et al 2010;Diele-Viegas et al 2020;Rozen-Rechels et al 2020). In Mexico, research studies focusing on the effects of climate change on reptiles, and specifically on lizards, have been increasing in the last decade (e.g., Sinervo et al 2017;Lara-Reséndiz et al 2019Domínguez-Guerrero et al 2020;Gadsden et al 2020).…”
Section: Introductionmentioning
confidence: 99%